Factors Hindering the Implementation of the Minister of Home Affairs Regulation No. 84 of 2015: A Study of Nendali Village, East Sentani District, Jayapura Regency, Papua Province - Toroby, Renida Joselina; Marani, Evelin Agustina; Fonataba, Isay E. M.; Muabuay, Esthina Isabella; Ilham, Ilham (Transpublika Publisher, 2025)
The implementation of national policies at the village level is crucial for effective local governance and community development. In Indonesia, Minister of Home Affairs Regulation No. 84 of 2015 was established to standardize and professionalize village governance structures and procedures. An analysis is conducted of the factors influencing the implementation of Minister of Home Affairs Regulation No. 84 of 2015 in Nendali Village, East Sentani District, Jayapura Regency. A qualitative approach was employed, wherein data were sourced from observation, interviews, and literature studies. The results of the study show that policy implementation is quite effective thanks to good communication and coordination between village officials and strong local socio-cultural support. Despite limited resources and irregular guidance, the village government has been able to optimize the allocation of funds for training officials and institutional activities. Papuan cultural values, such as kinship and traditional leadership, have proven to strengthen community participation and the legitimacy of village administration. Thus, The confluence of endemic cultural norms and modern governance paradigms functions as a contributory factor to efficacious policy implementation in village settings.